A Sacral Mass in a Newborn: A Variant of Type II Diastematomyelia with Triple Splitting of the Cord. (8th May 2013) - Shatla, Emad Sadek; Bedair, El Said M. A.; Soliman, Ashraf
Abstract : Ultrasonographic (US) evaluation of spinal anomalies is limited. MRI is increasingly being used in the diagnosis of spinal anomalies. MRI has been able to show clearly the detailed anatomy of this rare case of type II diastematomyelia with triple splitting of the cord.